Ferulic Acid Alleviates Radiation-Induced Immune Damage by Acting on JAK/STAT Signaling Pathway - Mingyue Huang; Anping Ye; Haoyu Zhang; Junru Chen; Tingyu Yang; Xue Wei; Yue Gao; Zengchun Ma (Pharmaceuticals)
The disruption of hematopoietic and immune functions is a significant consequence of the long-term effects of radiation exposure. This study investigated the potential mechanisms by which ferulic acid (FA) acts as a radioprotective agent in mitigating radiation-induced immune damage. C57BL/6J mice were exposed to a dose of 6.0 Gy of 60Co γ irradiation. FA was administered at doses of 25, 50, and 100 mg/kg/d for 7 days before and 30 days following irradiation. We evaluated changes in peripheral blood cells, T and B lymphocytes, natural killer cells in the spleen, and hematopoietic stem/progenitor cells in the bone marrow (BM). Whole-genome transcriptome sequencing of BM was performed to explore potential mechanisms. FA administration resulted in a significant reduction in malonaldehyde levels (p < 0.0001), an increase in catalase and beta-nicotinamide adenine dinucleotide levels in serum (p < 0.05), and enhanced multipotent progenitors (p < 0.01) and common lymphoid progenitors (p < 0.05) in the BM. Additionally, there was an elevation in white blood cell levels, red blood cell levels, and hemoglobin levels in peripheral blood (p < 0.01). Transcriptome analysis indicated that FA reversed the radiation-induced expression of genes related to immunity and inflammation. Enzyme-linked immunosorbent assay experiments further demonstrated that FA reduced interleukin-6 levels in the BM and decreased JAK1, JAK2, and STAT3 protein content (p < 0.01). In conclusion, FA might mitigate hematopoietic and immune damage by modulating the JAK/STAT signaling pathway.